Evaluation of prescription indicators established by the WHO in Getúlio Vargas - RS - Andressa Tanise Vooss; Helissara Silveira Diefenthaeler (Universidade de São Paulo, 2011)
To evaluate the conditions of the services offered to the community regarding medications, the World Health Organization (WHO) has developed the Medication Use Indicators, among them Prescription indicators. The objective of this study was to evaluate drug prescriptions in a Basic Health Care Center in Getúlio Vargas - RS, according to the Prescription Indicators recommended by the WHO. The data collection was performed with the use of a form and the prescriptions for June / July and November / December 2008 were evaluated. The average number of drugs prescribed was 2.03, and 72.8% of the drugs were prescribed by generic name, 80.3% were on the list of essential drugs, 21.7% were antibiotics and 2.4% were injectable drugs. The results were in accordance with WHO recommendations and were similar to those reported by other studies. Para avaliar as condições dos serviços prestados à população no que se refere aos medicamentos, a Organização Mundial da Saúde (OMS) desenvolveu Indicadores do uso de Medicamentos, entre eles os de Prescrição. O objetivo da pesquisa foi avaliar prescrições medicamentosas de usuários de uma Unidade Básica de Saúde do município de Getúlio Vargas - RS conforme os Indicadores de Prescrição preconizados pela OMS. A coleta de dados foi realizada com uma ficha. Para isso houve acesso as prescrições atendidas no período de junho/julho e de novembro/dezembro de 2008. A média de medicamentos prescritos foi de 2,03, 72,8% dos medicamentos foram prescritos pelo nome genérico, 80,3% constavam na lista dos medicamentos essenciais, 21,7% eram antibióticos e 2,4% injetáveis. Observou-se que os resultados obtidos estão de acordo com os recomendados pela OMS e que foram similares a outros estudos.